Grand Societal Challenges and Responsible Innovation - Voegtlin, Christian; Scherer, Andreas Georg; Stahl, Günter K.; Hawn, Olga (Journal of Management Studies, 2022)
AbstractGrand societal challenges (GSCs) represent complex, multi‐level, multi‐dimensional problems that require concerted efforts by various actors – public, private, and non‐profit – to be successfully addressed. Businesses – alone or in conjunction with governmental and non‐profit organizations – are relevant actors in this regard, as they represent a source of innovation. Responsible innovation (RI) is a framework that allows for the governance and evaluation of innovations with regard to their potential harmful consequences and positive contributions to societal challenges. Moreover, it stipulates that this evaluation process should be facilitated by appropriate governance structures at various levels. The aim of this article is to expand theorizing on GSCs and RI and to encourage research that explores their links. We outline pertinent characteristics of GSCs that make current conceptualizations of corporate social responsibility and social innovation limited in addressing GSCs. We explicate the reflexive and participative capacities of RI governance as a complementary and promising way forward. Finally, we introduce the contributions to this Special Issue as illustrations of relevant theoretical and empirical groundwork around GSCs and RI, and outline the agenda for future research.